Autosomal dominant polycystic kidney disease. Issue 10174 (2nd March 2019) - Cornec-Le Gall, Emilie; Alam, Ahsan; Perrone, Ronald D
Summary: Autosomal dominant polycystic kidney disease (ADPKD) is the most common hereditary kidney disease and one of the most common causes of end-stage kidney disease. Multiple clinical manifestations, such as enlarged kidneys filled with growing cysts, hypertension, and multiple extrarenal complications, including liver cysts, intracranial aneurysms, and cardiac valvular disease, show that ADPKD is a systemic disorder. New information derived from clinical research using molecular genetics and advanced imaging techniques has provided enhanced tools for assessing the diagnosis and prognosis for individual patients and their families. Phase 3 randomised, placebo-controlled clinical trials have clarified aspects of disease management and a disease-modifying therapeutic drug is now available for patients with high risk of rapid disease progression. These developments provide a strong basis on which to make clear recommendations about the management of affected patients and families. Implementation of these advances has the potential to delay kidney failure, reduce the symptom burden, lessen the risk of cardiovascular complications, and prolong life.